Hasan Bari DT Bagindo Rajo Pejuang PRRI DI Kuranji Kota Padang (1958-1961) - Muhammad Alseprianto; Etmi Hardi (Jurusan Sejarah FIS UNP, 2020)
Hasan Basri is a warrior From the Jappanese era until the PRRI uphevelin the city of Padang, in the articel thematic biography. This study analyzes the role of Hasan Basri as the comander pleton Reculer in the up[heavel in the City of Padang. This study uses the Historical method of the Heuristic proces, or the collection of sources and then proceed with the process of source criticism and data interpretation.The last stand is the writingof history so that this biography can be completed.the result showed that the attack on the land of Kuranjiwas faced by Hasan Basri agains the central army until finnalythe PRRI troops continued to recede toward the Lubuk Minturun. After the meetingin pariaman in the atmosphereof the PRRI upheavel, it was decided to form five Battalions under the Devision of devisi Banteng . Hasan Basri who has a hard attitude and will never back down to fight to Lubuk Alung and Solok by bringging his wife and children. The strunggle of Hasan Basri must end with his surrender to the headquarters of the central army so that he is sworn in to return to to the lap ibu pertiwi.